Inclusive leadership and employee voice behaviour: Serial mediating effects of psychological safety and affective commitment - Olawale Fatoki (Administrative Sciences, 2024)
Leaders have an important role to play in the creation of an organisational climate that fosters learning, engagement and voice behaviour. This study investigated the effect of inclusive leadership on the voice behaviour of the employees of small hospitality firms in South Africa. In addition, this study examined the serial mediating effects of psychological safety and affective commitment. To the best of the author's knowledge, this is one of the primary studies to explore the sequential mechanism through which inclusive leadership impacts employee voice behaviour. This study used a quantitative research design, and data were collected from employees in a cross-sectional survey. This study adopted the convenience sampling method, and SPSS AMOS27 was used for structural equation modelling. The findings indicated the positive effect of inclusive leadership on employee voice behaviour. In addition, this study confirmed the serial mediating roles of psychological safety and affective commitment. The findings of this study contribute to a deeper understanding of the factors that can promote employee voice in hospitality firms through the testing of a new theoretical model. The findings of this study have important implications for policy and practice in the hospitality industry.
Keywords: 350; affective commitment; hospitality firms; inclusive leadership; psychological safety; voice behaviour